2011
DOI: 10.2166/washdev.2011.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and verification of four field-based microbiological tests: H2S test, Easygel®, Colilert®, Petrifilm™

Abstract: The UN defines water supplies as ‘improved’ or ‘unimproved.’ These indicators are easy to measure, but do not reflect water quality, which requires laboratory or field tests. Laboratory and test availability, expense and technical capacity are obstacles for developing countries. This research compares and verifies four low-cost, field-based microbiological tests: the EC-Kit (Colilert® and Petrifilm™ tests), the H2S bacteria test, and Easygel®, against a standard method (Quanti-Tray®). The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Therefore a certification mechanism must be implemented for the H 2 S strip test based monitoring, similar in scope and format to the South African Scoring System certification [110]. Recent data from the Philippines and the USA compared reliability of the Colilert TM system and the H 2 S strip test based that the medium of Venkobachar et al [37,111]. For the WHO-defined improved and unimproved sources of drinking water, the Colilert TM system correctly predicted faecal contamination in 75% of 521 samples taken from drinking water sources similar to the ones used in South Africa [111].…”
Section: Faecal-source Tracking and Proposed Changes To The Existimentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore a certification mechanism must be implemented for the H 2 S strip test based monitoring, similar in scope and format to the South African Scoring System certification [110]. Recent data from the Philippines and the USA compared reliability of the Colilert TM system and the H 2 S strip test based that the medium of Venkobachar et al [37,111]. For the WHO-defined improved and unimproved sources of drinking water, the Colilert TM system correctly predicted faecal contamination in 75% of 521 samples taken from drinking water sources similar to the ones used in South Africa [111].…”
Section: Faecal-source Tracking and Proposed Changes To The Existimentioning
confidence: 99%
“…On the other hand, the H 2 S strip test performed best if the manually-prepared sampling kits were used and the sample size was equal to 20 mL [18,111]. In that case, 84% of 521 samples were correctly identified as faecally-contaminated in the H 2 S strip test, while the rate of false positive results was equal to 10% [111].…”
Section: Faecal-source Tracking and Proposed Changes To The Existimentioning
confidence: 99%
See 2 more Smart Citations
“…The kit combines two tests: (1) the Cohlert 10 mL presence/absence test; and (2) the Petrifilm test that provides a quantitative count of E. coli colonies (see Chuang et al (2011) for a detailed description, evaluation and comparison of these tests in a developing country context). The Colilert test indicated that 69 out of the 118 water samples collected (58.5%) were contaminated with E. coli.…”
Section: Performance Of Water Systemsmentioning
confidence: 99%